Reverse Logistics in Pharmaceutical Industry - Malik Iqbal Kabir (International Journal of Supply Chain Management, 2013)
This study looks into detailed aspects of reverse logistics on the issues that pharmaceutical organizations face. Reverse logistics is now following a trend where it is seen as a competitive advantage and a source of potential revenue. The perception is changing from the tradition of returns being a barrier to profits and a cost burden. Also the sustainability issue being addressed by reverse logistics is beneficiary to pharmaceutical organizations with end-of life products. The discussion contributed to the market perspective and to back up the misconception of returns being a cost issue, when it maintains market share by retaining quality. The perception of those industry practices on the environment and sustainability practiced by organizations has shown less enthusiasm than once thought.